The Clinical report of Asthmatic Patients with CVA by treatment of Homins Placenta Aqua-Acupuncture - EunGon Kim; Sung-Kyun Kim; Jong-Hyun Han; Shim YunSueb; Lee JungHee (Korean Pharmacopuncture Institute, 2004)
Nowadays Asthma is considered to be an inflamatory disease characterized by airway hyperresponsiveness and pulmonary eosinophilia. Hominis Placenta is the dried placenta of a healthy women. It has correspondence to the meridians of lung and kindey. Hominis Placenta acupuncture therapy has effect on invigoration of vital energy nourishing blood and tonifying the essence. It can be applied to the disease as Asthma, pulmonary tuberculosis, chronic hepatitis, liver cirrhosis, degenerative change and cerebrovascular disease. We treated two patients of Asthma with CVA by Homins Placenta Aqua-Acupuncture. The effect of Homins Placenta Aqua-Acupuncture was assessed by analyzing the pulmonary function test(PFT) and Quality of Life Questionnaire for adult Korean Asthmatics(QLQAKA) in patients before and after treatment. Total score was increased. The patients are satisfied our treatment. But further research concerning this is still necessary.